Meningkatkan Kemampuan Otak Anak Melalui Media Audio Visual Pada Anak Usia 5-6 Tahun di TK Kemala Bhayangkari 01 Kota Kupang - Kale, Sartika; Passio, Ephifania Tressie; Lawe, Elisa; Ama, Elisabeth Norama; Lima, Dorothea; Seo, Daris; Liu, Elda Desilva; Tefnai, Delsina; Mali, Ermalisa Oknalia (Universitas Nusa Cendana, 2024)
The use of video media can improve children's ability to learn, and learning activities involve thinking skills that can sharpen children's brains. Through audio-visual media, the learning material to be delivered is able to arouse the enthusiasm of students to learn through the images, sounds and animations presented, so as to increase learning motivation and student learning outcomes. The methods used in the implementation of this activity are observation, question and answer and discussion. The activity carried out is the screening of a film entitled